A Nano‐Wrinkled Zn0.92Fe0.08O Thin Film Developed Using a High‐RPM Electro‐Spin Patterning Technique via Sol‐Gel Route For Methane Sensing. Issue 42 (13th November 2018) - Anchal, Brij Bansh Nath; Singh, Preetam; Pyare, Ram
Abstract: The development of superior methane sensors is important to insure the safety of laborers working in coal field/mine and CNG fuel stations as methane is not only the explosive gas but also act at asphyxiant and the leakage of methane is cause of tragic death of laborers working in coal mines/fields. We reports the development of nano‐wrinkled thin film of 8% iron doped zinc oxide (Zn0.92 Fe0.08 O) deposited by high rpm electro‐spin patterns technique for superior methane sensing performance. The method of deposition, developed/utilized here is very easy to perform in order to develop the films of same quality repetitively. Our developed Zn0.92 Fe0.08 O film showed high activity with quick response for methane sensing because of the increased active adsorption sites due to wrinkled structures grown at the surface of the thin films. The Thin film was characterized by XRD, SEM, EDX and AFM. These characterizations confirm the film structures, grain sizes, roughness and its crystal structure. The film showed high sensitivity for methane in the range of 100 to 500 ppm in the temperature range of 75 °C to 200 °C. Abstract : Nano‐wrinkled film of 8% Fe doped ZnO was synthesised using modified high rpm spin coating method via chemical route. Architecting nano‐wrinkled structure thin film contains high active surface area for chemisorptions resulting into high sensitivity of the film for Methane sensing and detection. The enhance sensitivity of the thin film is also result of n‐type Fe‐ion doping in ZnO structure resulting high carrier concentration.